(untitled) (American Journal of Business Management, Economics and Banking, 2025)
The study examined Corporate Financial Strategy in a Digitally Disrupted Economy: A theoretical Review. The objectives of the study were to determine the effect of AI on long-term investment decision making, to ascertain the effect of cloud-based enterprise resource planning on long-term cash flow management, and to assess the effect of automated financial planning on long-term investment financing. The study identified that the use of digital tools enhances corporate financial strategy by shifting the finance function from reactive, manual reporting to proactive, data-driven value creation. The study concludes that the application of digital tools is necessary for effectively enhancing corporate financial strategy because they drive significant improvements in operational efficiency, decision-making, and financial accuracy. The study recommends that in order to make successful long-term investment decision in a digitally disrupted economy, AI should be used in determining corporate financial strategy. Successful long term cash management should be made possible through the use of cloud-based enterprise resource planning in a digitally disrupted economy. Effective long term investment financing should be executed with automated financial planning technology in a digitally disrupted economy